TRPM7 Kinase Is Essential for Neutrophil Recruitment and Function via Regulation of Akt/mTOR Signaling - Nadolni, Wiebke; Immler, Roland; Hoelting, Kilian; Fraticelli, Marco; Ripphahn, Myriam; Rothmiller, Simone; Matsushita, Masayuki; Boekhoff, Ingrid; Gudermann, Thomas; Sperandio, Markus; Zierler, Susanna (Frontiers in Immunology, 2021)
During inflammation, neutrophils are one of the first responding cells of innate immunity, contributing to a fast clearance of infection and return to homeostasis. However, excessive neutrophil infiltration accelerates unsolicited disproportionate inflammation for instance in autoimmune diseases such as rheumatoid arthritis. The transient-receptor-potential channel-kinase TRPM7 is an essential regulator of immune system homeostasis. Naïve murine T cells with genetic inactivation of the TRPM7 enzyme, due to a point mutation at the active site, are unable to differentiate into pro-inflammatory T cells, whereas regulatory T cells develop normally. Moreover, TRPM7 is vital for LPS-induced activation of murine macrophages. Within this study, we show that the channel-kinase TRPM7 is functionally expressed in neutrophils and has an important impact on neutrophil recruitment during inflammation. We find that human neutrophils cannot transmigrate along a CXCL8 chemokine gradient or produce reactive oxygen species in response to gram-negative bacterial lipopolysaccharide LPS, if TRPM7 channel or kinase activity are blocked. Using a recently identified TRPM7 kinase inhibitor, TG100-115, as well as murine neutrophils with genetic ablation of the kinase activity, we confirm the importance of both TRPM7 channel and kinase function in murine neutrophil transmigration and unravel that TRPM7 kinase affects Akt1/mTOR signaling thereby regulating neutrophil transmigration and effector function. Hence, TRPM7 represents an interesting potential target to treat unwanted excessive neutrophil invasion.